Grammer of politics - Laski, Harold J. (London, 1938)
This book intends to discuss about the entire organogram of politics and political institutions. It has been designed keeping in view the conceptual clarification as well as the notions and functions of different political institutions. Various political concepts as enshrined here form the basis of modern political institutions, putting special emphasis on state. Commendably, the aspects that caused the emergence of state have been given due importance. It is inborn habit of every human being to live with fellow-friends. As a result, society has been evolved. With the passage of time, the utterances of society have led its people forming different institutions in order to meet the demands. Once, this approach has imbued people to build a particular civilisation. The process of civilisation takes a long duration. During this period, people develop different notions and principles in regard to their lives. Ultimately, a political system brought about to nourish and preserve the interests of the society. There is nothing denying that the purpose of the state is to safeguard the life and property of the individuals. Relevantly, it has been the agreed trend that modern democratic states asserts and acknowledges that without the orientation of socialism, i.e. ensuring rights and privileges of every people; the efforts of state activities would be meaningless. Every dealings that cover the necessities of human life entails on politics. So, it discusses as to other social and economic institutions protecting the interests of the people. For the subsistence of human being in the society and preserving the social structure intact, protection of the right of the people is essential. So, emergence of judiciary has been necessitated. As the states are aimed at ensuring the human comfort, the public administration is being well- structured to provide the citizens better service. Efficient public service accomplishes the aims and objectives of the state. In addition, for the stability and gradual development of state institutions, states are also to keep good terms with international community. Consequently, the relationships with international organizations are also being developed.
Keywords: Politics